2019
DOI: 10.1002/app.48179
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinylidene fluoride) membranes fabricated by vapor‐induced phase separation (VIPS) for the adsorption removal of VB12 from aqueous solution

Abstract: Poly(vinylidene fluoride) (PVDF) membranes without any additives were fabricated by a vapor-induced phase separation method and applied to the adsorption separation of vitamin B12 (VB12) from aqueous solution. The effects of preparation conditions including PVDF concentration in dope, vapor humidity, and exposure time on the morphologies, mechanical strength, adsorption, and permeation performances are investigated in detail. The results indicate that the PVDF membranes have a uniform spongy structure without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Notably, Producers accounted for only a small portion (15.5%) of the total detected MAGs, and only 1.0% of MAGs were classified as Very-Likely-Producers that contained a complete set of cobamide biosynthesis genes, while the majority of the observed MAGs were predicted to use cobamides. These results indicated that cobamides were widely shared between strains in WWTP systems, and the majority of prokaryotes use an external source, supplied by either the biosynthesis of surrounding cohorts or the low concentration residual from effluent wastewater. , And the high demand and supply rate (≈6.3:1) of cobamides inferred the significance of cobamide production microbes in the microbial community of WWTP systems.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Notably, Producers accounted for only a small portion (15.5%) of the total detected MAGs, and only 1.0% of MAGs were classified as Very-Likely-Producers that contained a complete set of cobamide biosynthesis genes, while the majority of the observed MAGs were predicted to use cobamides. These results indicated that cobamides were widely shared between strains in WWTP systems, and the majority of prokaryotes use an external source, supplied by either the biosynthesis of surrounding cohorts or the low concentration residual from effluent wastewater. , And the high demand and supply rate (≈6.3:1) of cobamides inferred the significance of cobamide production microbes in the microbial community of WWTP systems.…”
Section: Discussionmentioning
confidence: 91%
“…These results indicated that cobamides were widely shared between strains in WWTP systems, and the majority of prokaryotes use an external source, supplied by either the biosynthesis of surrounding cohorts 17 or the low concentration residual from effluent wastewater. 19,58 And the high demand and supply rate (≈6.3:1) of cobamides inferred the significance of cobamide production microbes in the microbial community of WWTP systems.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation